Water Buffaloes grazing behaviour at the Lake Kerkini National Park, Northern Greece - Tsiobani, Eleni T.; Yiakoulaki, Maria D.; Hasanagas, Nikolaos D.; Menexes, Georgios; Papanikolaou, Konstantinos (Hacquetia, 2016)
The monthly variation of Greek water buffaloes’ grazing behaviour was investigated at the Lake Kerkini National Park in Greece. Direct observations were carried out on six female buffaloes for two consecutive days every month for a one-year period, and the time spent (in minutes) on their grazing-related activities (feeding, moving, wallowing, standing, ruminating, drinking, and lying) was recorded. Moreover, social and aggressive interactions and selfgrooming were recorded as number of events. Also, the daily distance travelled by buffaloes was recorded with a handheld GPS. Buffaloes travelled on average 6.9 km/day, and they walked their longest distance in June (10.7 km/day) and their shortest in September (2.9 km/day). They spent more time (P<0.05) on feeding (309.2 min/day) compared to moving (121.7 min/day), wallowing (27.9 min/day), standing (20.2 min/day), ruminating (15.4 min/day), drinking (4.7 min/day) and lying (4.2 min/day). Greek water buffaloes seem to be sociable rather than aggressive animals as they devote to these activities on average 18.2 vs 0.5 events/day. We can conclude that the animals adjust their grazing behaviour to climatic conditions and the availability of forage resources.